Candida Antifungal Resistance and Therapeutic Approach - Francisca Vieira; Teresa Nascimento (Revista Portuguesa de Farmacoterapia, 2017)
Species from genus Candida are characterized by their opportunistic nature and can trigger several infections, especially in immunocompromised hosts. The emergence of non-albicans Candida species, associated with high morbidity and mortality rates, is largely associated with the mechanisms of resistance, intrinsic or acquired, to the conventionally antifungal agents used. Their understanding is fundamental for the development of effective therapeutic approaches. The diagnosis and treatment of these infections poses to be a real challenge and treatment should be implemented as soon as possible. However, on one hand the empirical use of antifungal agents correlates with increased resistance of non-albicans Candida species, on the other hand the antifungal susceptibility testing acts as an auxiliary for targeted therapy, and it is implicit a reduction in the development of resistant species.